ANALISIS PENGARUH DISIPLIN KERJA, PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Werdiasih, Rustina Dewi; Lilis Barokah (JURNAL EKONOMI, 2018)
This research has aims to analyze partially and simultaneously: 1) the influence of work discipline on employee performance, 2) the influence of career development on employee performance, 3) the effect of compensation on employee performance, 4) the influence of work discipline, career development and compensation on employee performance . The type of research used is survey research. This study took place at Bank BRI Gandrung Mangu and Bantarsari, this study uses 30 employees as respondents research. Proof of this research hypothesis using multiple linear regression. The results of this study were 1) the work discipline discount a significant influence on employee performance 2) the career development has no significant influence on employee performance 3) compensation does not have a significant effect on employee performance 4) discipline of work, career development and compensation have a significant influence on the employee performance. Keywords: Work Discipline, Career Development, Compensation, Employee Performance.